Respiratory epithelial adenomatoid hamartoma of the anterior nasal septum a rare localisation of an unusual tumour in a child: a case report - Gajda, Mariusz (Cases Network Ltd, 2009)
INTRODUCTION: Hamartomas are non-neoplastic lesions constituted by a mixture of tissues indigenous to the region. Respiratory epithelial adenomatoid hamartomas are characterised by glandular proliferation lined by ciliated airway epithelium. Their localisation in the nasal cavity is rare and most frequent cases described so far were associated with the posterior nasal septum. CASE PRESENTATION: A 9-year-old Caucasian boy presented with long-standing nasal obstruction. A large right nasal mass was evident on physical and CT examinations. It was surgically removed from the anterior nasal septum under general anaesthesia. Histologically, the diagnosis of REAH was established. The tumour lined by stratified squamous and ciliated respiratory epithelium was characterised by prominent glandular proliferation. By immunohistochemistry, the tumour was positive for cytokeratins, smooth muscle actin, vimentin, laminin, collagen type IV, CD8, and CD68. No S-100 immunoreactivity was observed. The patient has been asymptomatic for 12 months with completely healed lining of the nose. CONCLUSION: Respiratory epithelial adenomatoid hamartoma, although rare, must be taken into consideration in differential diagnosis of nasal exophytic lesions.